Multiculturalism and the Politics of Recognition:Jacques Derrida and James Tully - Bielskis, Andrius (Sociologija. Mintis ir veiksmas, 2009)
This essay critically engages Jacques Derrida’s and James Tully’s theoretical conceptualizations of multiculturalism and the politics of recognition. It analyzes the possibilities of using deconstruction when reflecting the nature of law and violence as well as how an aporia, revealed by deconstruction, provides us with an alternate understanding of the politics of recognition. James Tully’s Wittgensteinian critique of modern constitutionalism is analysed in the context of (and compared to) Derrida’s deconstruction of law, showing that both social theorists understand multiculturalism and the politics of recognition as an ongoing and open-ended process.